Iyawo Ile as a Traditional Peacemaking Institution among the Yoruba Wives of Southwestern Nigeria - Agbaje , Funmilayo Idowu (Àgídìgbo: ABUAD Journal of the Humanities, 2020)
Yoruba women have always played a unique role in the reconciliation and peace process in the extended family in traditional society as a whole, and that this puts them in a strong position to encourage dialogue between disputing parties. However, much work still needs to be done in regard of the role of women as peacemakers in traditional family settings in Africa. This study appraises the Iyawo Ile traditional institution in Yoruba as the transmitters of peace values through the use of diplomatic measures such as secrecy, negotiation and respect for the elders.